Baclofen in the Treatment of Patients With Alcohol Use Disorder and Other Mental Health Disorders - Agabio, Roberta; Leggio, Lorenzo (Frontiers in Psychiatry, 2018)
A limited number of medications are approved to treat Alcohol Use Disorder (AUD). Furthermore, the magnitude of their therapeutic effect is relatively modest, suggesting the potential for sub-types of patients who respond to a specific medication. The use of these medications is also limited in clinical practice by a series of contraindications such as medical comorbidities and/or concurrent use of other medications. In recent years, animal and human studies have been conducted to evaluate the efficacy of baclofen, a GABAB receptor agonist approved for clinical use as a muscle relaxant, in the treatment of AUD. However, some of these studies have yielded contrasting results. Despite this discrepancy, baclofen is often used off-label to treat AUD, especially in some European countries and Australia. Recently, several factors have been considered to try to shed light on the potential reasons and mechanisms underlying the inconsistent results obtained until now. The presence of a psychiatric comorbidity may be amongst the abovementioned factors playing a role in explaining different responses to baclofen treatment in terms of alcohol drinking outcomes. Therefore, the aim here was to conduct a narrative review of the scientific literature related to the use of baclofen in AUD both in patients with and without concomitant psychiatric disorders. All clinical studies (randomized and controlled, open-label, retrospective, human laboratory studies and case reports) were analyzed and discussed, bearing in mind other potential factors that may have influenced baclofen response, including dose administered, severity of AUD, use of other psychosocial therapies and the presence of physical disorders. This review indicates that the most frequent psychiatric comorbidities in patients affected by AUD undergoing baclofen treatment are anxiety and mood disorders. Unfortunately, no definitive conclusions can be drawn due to the lack of specific analyses on whether baclofen efficacy is different in AUD patients with comorbid psychiatric disorders versus those without. Therefore, it will be critical that psychiatric comorbidities are taken into account in the planning of future studies and in the analysis of the data with the ultimate goal of understanding whether subtypes of AUD patients may respond best to baclofen.